Proposta de um sistema de controle e automação hidráulico residencial de baixo custo utilizando a plataforma Open Source Arduino - OLIVEIRA, Marcus Vinícius Miranda de (2019)
The objective of this work is the development of a low cost hydraulic control and automation system of a residential, through a local supervisor using the free Arduino prototyping platform. Desiring to seek simplicity and comfort for the user, this system seeks to solve routine problems due to the lack of supervision and interruption of the residential water supply in question, where it was possible to verify several irregularities that generated wastage of resources and inconveniences for all those who used them daily the same. The autonomous control and monitoring system has as main functions: Control and automate the process of supply and residential hydraulic supply; Reduce costs through the rational use of electricity and water; Monitor the system through the use of sensors and access information through an HMI.